Digitalisasi Transaksi Pemasukan dan Pengeluaran Kas di Kafe View Pacific Garden - Pertiwi, Dian; Sejati, Fajar Rina; Tonggiroh, Mursalim; Lina, Ros (Jurnal Abdi Masyarakat Nusantara, 2023)
Abstract: Poor financial management will make it difficult for MSMEs to make appropriate business decisions. Especially in the face of difficulties during the pandemic. The availability of financial information can be one of the factors that help the success of MSMEs. Thus, the purpose of this service program is to improve the recording of MSME transactions and make them available in digital form. The method of this service program is mentoring, which is providing directions on how to input transactions data of cash income and cash disbursement into the application. After the assistance has been carried out, the business owner, in this case the VPG Café, has been able to input transactions data into the application. In addition, digital financial information is available that can be accessed anytime and anywhere. With the implementation of this program, it is hoped that it can improve financial and business management of VPG Cafe owners so that business continuity continues for a long time. Keywords: Digitization; Cash Income; Cash Disbursement; MSME